The Pharmacotherapy of Chronic Pain: A Review - Mary E Lynch; C Peter N Watson (Pain Research and Management)
The past two decades have contributed a large body of preclinical work that has assisted in our understanding of the underlying pathophysiological mechanisms that cause chronic pain. In this context, it has been recognized that effective treatment of pain is a priority and that treatment often involves the use of one or a combination of agents with analgesic action. The current review presents an evidence-based approach to the pharmacotherapy of chronic pain. Medline searches were done for all agents used as conventional treatment in chronic pain. Published papers up to June 2005 were included. The search strategy included randomized, controlled trials, and where available, systematic reviews and meta-analyses. Further references were found in reference sections of papers located using the above search strategy. Agents for which there were no controlled trials supporting efficacy in treatment of chronic pain were not included in the present review, except in cases where preclinical science was compelling, or where initial human work has been positive and where it was thought the reader would be interested in the scientific evidence to date.